Apo A1 Mimetic Rescues the Diabetic Phenotype of HO-2 Knockout Mice via an Increase in HO-1 Adiponectin and LKBI Signaling Pathway. (4th April 2012) - Cao, Jian; Puri, Nitin; Sodhi, Komal; Bellner, Lars; Abraham, Nader G.; Kappas, Attallah
Abstract : Insulin resistance, with adipose tissue dysfunction, is one of the hallmarks of metabolic syndrome. We have reported a metabolic syndrome-like phenotype in heme oxygenase (HO)-2 knockout mice, which presented with concurrent HO-1 deficiency and were amenable to rescue by an EET analog. Apo A-I mimetic peptides, such as L-4F, have been shown to induce HO-1 expression and decrease oxidative stress and adiposity. In this study we aimed to characterize alleviatory effects of HO-1 induction (if any) on metabolic imbalance observed in HO-2 KO mice. In this regard, HO-2 (−/−) mice were injected with 2 mg/kg/day L-4F, or vehicle, i.p., for 6 weeks. As before, compared to WT animals, the HO-2 null mice were obese, displayed insulin resistance, and had elevated blood pressure. These changes were accompanied by enhanced tissue (hepatic) oxidative stress along with attenuation of HO-1 expression and activity and reduced adiponectin, pAMPK, and LKB1 expression. Treatment with L-4F restored HO-1 expression and activity and increased adiponectin, LKB1, and pAMPK in the HO-2 (−/−) mice. These alterations resulted in a decrease in blood pressure, insulin resistance, blood glucose, and adiposity. Taken together, our results show that a deficient HO-1 response, in a state with reduced HO-2 basal levels, is accompanied by disruption of metabolic homeostasis which is successfully restored by an HO-1 inducer.